Out-of-phase thermomechanical fatigue crack propagation in a steam turbine steel — Modelling of crack closure. (August 2021) - Azeez, Ahmed; Norman, Viktor; Eriksson, Robert; Leidermark, Daniel; Moverare, Johan
Highlights: Crack growth testing of out-of-phase thermomechanical fatigue (100–600 °C). Crack closure below zero nominal stress in all strain controlled tests. Accounting for crack closure collapses the crack growth rates together. An isothermal fatigue crack growth test at 100 °C agreed with the collapsed curves. Finite element modelling with stationary crack predicted crack closure levels. Abstract: Understanding of crack growth behaviour is necessary to predict accurate fatigue lives. Out-of-phase thermomechanical fatigue crack propagation tests were performed on FB2 steel used in high-temperature steam turbine sections. Testing results showed crack closure where the compressive part of the fatigue cycle affected crack growth rate. Crack closing stress was observed to be different, and had more influence on the growth rate, than crack opening stress. Crack growth rate was largely controlled by the minimum temperature of the cycle, which agreed with an isothermal crack propagation test. Finite element models with stationary sharp cracks captured the crack closure behaviour.